Fibrous mesoporous silica perovskite composite material and preparation method thereof
The fibrous mesoporous silica perovskite composite material was prepared by sol-gel method and in-situ thermal injection method, which solved the stability and agglomeration problems of composite materials in the prior art, and achieved higher photothermal oxygen stability and application performance.
Patent Information
- Application Number
- CN202510020421.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The prior art is difficult to prepare CsPbBr3 perovskite quantum dot composite materials with adjustable morphology and size, more uniform storage, more uniform distribution and more stable combination, resulting in stability and agglomeration problems in its application in optoelectronic devices such as LEDs.
Using the traditional sol-gel method and in-situ thermal injection method, composite materials with fibrous mesoporous silica and uniformly distributed perovskite quantum dots were prepared by using specific pore-forming agents and regulating the reaction temperature in the sol-gel reaction.
It improves the photothermal oxygen stability of perovskite quantum dots, reduces agglomeration phenomenon, and enhances the application performance of composite materials in the fields of photoelectric detection, solar cells and LEDs.
Smart Images

Figure CN119823748A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite materials, and in particular to a fibrous mesoporous silica perovskite composite material and a preparation method thereof. Background Art
[0002] In recent years, all-inorganic CsPbBr3 perovskite quantum dots have attracted more and more attention in LED devices, photodetectors, solar cells, etc. due to their high luminescent color saturation, adjustable optical band gap, and high quantum efficiency. However, due to the low lattice energy of CsPbBr3 and the strong ionicity of the crystal, stability is its most prominent disadvantage. Their luminescence is sensitive to humidity, temperature, light, etc., which can easily cause luminescence quenching. When it is applied to devices such as LEDs, the thermal effect generated will also quench its fluorescence; in addition, ion exchange is easy to occur between different quantum dots, causing their luminescence peaks to move, affecting the luminescence quality. Therefore, improving the stability of all-inorganic perovskite quantum dot materials and avoiding ion exchange between CsPbX3 quantum dots in device applications are hot spots and difficulties in this field.
[0003] Mesoporous silica is a porous material with a connected network pore structure and a large specific surface area. Compared with organic matrices, mesoporous silica has better chemical stability; compared with other inorganic matrices, mesoporous silica has better light transmittance and processing performance, and can be processed into any shape such as sheets, fibers, powders, etc. CsPbBr3 quantum dots are introduced into the pores of mesoporous silica, and the spatial confinement effect of the pores is used to prevent water molecules from entering the pores and improve their stability in the environment; and its nanopores can well disperse CsPbX3 quantum dots and reduce quantum dot agglomeration when LED devices are packaged. Therefore, the preparation of mesoporous silica perovskite composite materials is of great significance.
[0004] For example, the document Dirin DN, Protesescu L, Trummer D, et al. Harnessing Defect-Tolerance at the Nanoscale: Highly Luminescent Lead Halide Perovskite Nanocrystals in Mesoporous Silica Matrixes [J]. Nano Letters, 2016: 5866-5874. discloses a method for preparing mesoporous SiO2 perovskite quantum dots, which uses commercially available mesoporous silica (in spherical shape) to impregnate with a concentrated precursor solution in excess relative to the pore volume, and stirs in an inert gas and impregnates at room temperature for 10 minutes to obtain a mesoporous silica perovskite composite material with a size of 2.5 to 7 nm for CsPbBr3. However, since it is difficult to regulate the silica pore size and overall morphology with commercially available mesoporous silica, the size of the perovskite quantum dots generated by the precursor impregnation generation method is also uneven.
[0005] For example, in the literature Wang HC, Lin SY, Tang AC, et al. Mesoporous Silica Particles Integrated with All-Inorganic CsPbBr3 Perovskite Quantum-Dot Nanocomposites (MP-PQDs) with High Stability and Wide Color Gamut Used for Backlight Display [J]. Angewandte Chemie International Edition, 2016., commercially available mesoporous silica (in spherical form) was simply impregnated with CsPbX3 colloidal solution to prepare mesoporous silica perovskite quantum dot composite materials. However, this method can only enter perovskite quantum dots of a specific size, resulting in most of the pores being vacant and less perovskite being accommodated. And because it is a simple impregnation method, perovskite quantum dots are easily detached from the mesoporous silica pores.
[0006] How to prepare composite materials of CsPbBr3 perovskite quantum dots with adjustable morphology and size, more capacity, more uniform distribution and more stable bonding is of great significance for the application of CsPbBr3 in optoelectronic devices such as LEDs. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention discloses a fibrous mesoporous silica perovskite composite material, which has a novel microscopic morphology. The specific morphology can improve the photothermal and oxygen stability of perovskite quantum dots and improve the agglomeration phenomenon of perovskite quantum dots, and is expected to be deeply applied in the fields of photoelectric detection, solar cells, LEDs, etc.
[0008] The specific technical solutions are as follows:
[0009] A fibrous mesoporous silica perovskite composite material, comprising fibrous mesoporous silica and perovskite quantum dots grown in situ and uniformly distributed inside the pores of the fibrous mesoporous silica;
[0010] The fibrous mesoporous silica has a plurality of pores which are parallel to each other but not interconnected, and the pores are through holes along the length direction of the fibrous mesoporous silica;
[0011] The molecular formula of the perovskite quantum dot is CsPbX3, where X is selected from halogen.
[0012] The present invention also discloses a method for preparing the above-mentioned fibrous mesoporous silica perovskite composite material, comprising the following steps:
[0013] (1) fully hydrolyzing a silicon source precursor and a pore-forming agent under acidic conditions to undergo a crystallization reaction, and then calcining at a high temperature to obtain mesoporous silica;
[0014] The pore former is selected from a triblock copolymer of polyethylene oxide-polypropylene oxide-polyethylene oxide;
[0015] (2) mixing a cesium precursor, oleic acid and octadecene until completely dissolved to obtain a solution I, mixing a lead halide, oleic acid, oleylamine and octadecene until completely dissolved, and then adding the mesoporous silica prepared in step (1) to obtain a solution II;
[0016] (3) Rapidly injecting solution II into solution I, and obtaining the fibrous mesoporous silica perovskite composite material after sufficient reaction.
[0017] The present invention adopts a traditional sol-gel method and an in-situ hot injection method in two steps to prepare a composite material with a novel microscopic morphology. By using a specific pore-forming agent in the sol-gel reaction, a fibrous mesoporous silica with a plurality of pores parallel to each other but not interconnected inside can be prepared; and by regulating the reaction temperature, the size and order of the pore diameter in the mesoporous silica can be regulated, thereby controlling the light, heat and oxygen stability of the composite material finally prepared.
[0018] Comparative tests have shown that if other common pore-forming agents in the art (such as hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and dodecyltrimethylammonium bromide) are used in the sol-gel reaction, the prepared material will no longer be a fibrous mesoporous silica perovskite composite material. Further stability tests have shown that the stability of the composite material is also significantly reduced. If the crystallization temperature in the sol-gel reaction is too low, the prepared material will no longer be a fibrous mesoporous silica perovskite composite material. Further stability tests have shown that the stability of the composite material is also significantly reduced. The above conclusions all indicate that the excellent photothermal and oxygen stability of the composite material prepared in the present invention is closely related to the special fibrous micromorphology of the mesoporous silica used.
[0019] Preferred:
[0020] The length of the fibrous mesoporous silica is 300-850 nm, the diameter is 30-90 nm, and the average diameter of several pores in the fibrous mesoporous silica is 3-9 nm;
[0021] The size of the perovskite quantum dots is 4-6 nm.
[0022] Further preferred:
[0023] The length of the fibrous mesoporous silica is 400-600 nm, the diameter is 40-80 nm, and the average diameter of several pores in the fibrous mesoporous silica is 6-8 nm;
[0024] The size of the perovskite quantum dots is 4-5 nm.
[0025] Experiments have shown that with the continuous optimization of the above parameters, the photothermal and oxygen stability of the prepared fibrous mesoporous silica perovskite composite materials increases accordingly.
[0026] In step (1):
[0027] Preferably, the silicon source precursor is selected from one or more of tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane; more preferably, tetraethoxysilane.
[0028] Preferably, the mass ratio of the pore former to the silicon source precursor is 1:(1.5-2.5); more preferably, it is 1:(1.8-2.0).
[0029] Preferably, the pH value of the acidic condition is 1 to 2; the acidic condition is adjusted by adding an acidic substance commonly used in the art;
[0030] The acidic substance includes hydrochloric acid, sulfuric acid, nitric acid and the like.
[0031] Preferably, the raw material liquid is heated to ≥40°C for sufficient hydrolysis; more preferably 40-60°C.
[0032] Preferably, the temperature of the crystallization reaction is 85-125°C;
[0033] The experiment found that the temperature of the crystallization reaction (hydrothermal reaction) directly affects the microscopic size of the prepared fibrous mesoporous silica; as the crystallization reaction temperature increases, the order of the prepared fibrous mesoporous silica decreases; and when the crystallization reaction temperature is low, the resulting pore diameter is smaller;
[0034] In order to take into account both the order and the size of the pore diameter, it is further preferred that the temperature of the crystallization reaction is 100°C; experiments have found that the photothermal and oxygen stability of the fibrous mesoporous silica perovskite composite material prepared at this time is optimal.
[0035] Preferably, the high temperature calcination temperature is 400-700°C; more preferably 500-600°C.
[0036] In step (2):
[0037] Preferably, the cesium precursor is selected from cesium carbonate and / or cesium acetate;
[0038] Preferably, in the solution I, the concentration of the cesium precursor is 0.02 to 0.04 mol / L; more preferably, it is 0.025 to 0.035 mol / L.
[0039] Preferably, the molar ratio of the cesium precursor to oleic acid is 1:(10-15).
[0040] Preferably, the cesium precursor, oleic acid and octadecene are heated to ≥100°C to completely dissolve; more preferably, they are heated to 110-30°C.
[0041] In step (2):
[0042] Preferably, the lead halide is selected from one or more of lead fluoride, lead chloride, lead bromide and lead iodide; more preferably, lead bromide.
[0043] Preferably, in the solution II, the concentration of lead halide is 0.02 to 0.04 mol / L; more preferably, it is 0.025 to 0.035 mol / L.
[0044] Preferably, the mass ratio of lead halide to mesoporous silica is 1:(0.7-2.2); more preferably, it is 1:(1-1.5).
[0045] Preferably, the molar ratio of lead halide to oleic acid and oleylamine is 1:(10-15):(10-15).
[0046] In step (3):
[0047] Preferably, solution II is first heated to 185-195°C and then rapidly injected into solution I;
[0048] Preferably, the sufficient reaction time is 10 to 20 minutes.
[0049] Experiments have shown that the reaction time must be controlled more precisely. If the reaction time is too long, such as 40 minutes, the prepared product will no longer be CsPbX3.
[0050] Preferably, the volume ratio of solution I to solution II is 1:(10-15); more preferably, it is 1:(11-13).
[0051] The present invention also conducts light, heat and oxygen stability tests on the fibrous mesoporous silica perovskite composite material with special microscopic morphology prepared by the above method, proving that it has excellent stability.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention discloses a fibrous mesoporous silica perovskite composite material, which has a novel microscopic morphology. Perovskite quantum dots in the composite material are in-situ grown and evenly distributed inside the fibrous mesoporous silica pores. The composite material can not only give full play to the excellent performance of the perovskite quantum dots themselves, but also has excellent light, heat and oxygen stability.
[0054] The preparation method disclosed in the present invention adopts the traditional sol-gel method combined with the in-situ hot injection method, and can adjust the size and order of the pore diameter of the fibrous mesoporous silica through the production process parameters, thereby adjusting the light, heat and oxygen stability of the composite material finally prepared. The preparation process is simple and controllable, does not require additional equipment, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The XRD pattern of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0056] Figure 2 This is a SEM image of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0057] Figure 3 TEM image of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0058] Figure 4 HRTEM image of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0059] Figure 5 This is a pore diameter distribution diagram of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0060] Figure 6 Small angle X-ray scattering (SAXS) spectra of the fibrous mesoporous silica perovskite composite materials prepared in Examples 1, 2 to 4, respectively;
[0061] Figure 7 This is a curve showing the luminescence intensity variation over time of the fibrous mesoporous silica perovskite composite material prepared in Example 1;
[0062] Figure 8 The luminescence intensity of the fibrous mesoporous silica perovskite composite material prepared in Example 1 varies with temperature;
[0063] Fig. 9 This is the SEM image of the product prepared in Comparative Example 1;
[0064] Fig.10 The luminescence intensity of the product prepared in Comparative Example 1 changes with time;
[0065] Fig.11 TEM image of the product prepared in Comparative Example 2;
[0066] Fig.12 The XRD pattern of the product prepared in Comparative Example 3;
[0067] Fig.13 This is a TEM image of the product prepared in Comparative Example 4;
[0068] Fig.14 The luminescence intensity variation curve of the product prepared in Comparative Example 4 over time;
[0069] Fig.15 TEM image of the fibrous mesoporous silica perovskite composite material prepared in Example 2;
[0070] Fig.16 This is a pore diameter distribution diagram of the fibrous mesoporous silica perovskite composite material prepared in Example 3;
[0071] Fig.17 The luminescence spectrum of the fibrous mesoporous silica perovskite composite material prepared in Example 3 changes with time;
[0072] Fig.18 This is a pore diameter distribution diagram of the fibrous mesoporous silica perovskite composite material prepared in Example 4;
[0073] Fig.19This is a curve showing the luminescence spectrum of the fibrous mesoporous silica perovskite composite material prepared in Example 4 changing with time. DETAILED DESCRIPTION
[0074] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0075] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0076] Example 1
[0077] (1) 2 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) and 4.17 mL of tetraethoxysilane (TEOS, 3.9 g) were fully stirred in 15 mL of water, the pH was adjusted to 1.5 with 60 mL of hydrochloric acid aqueous solution (2 mol / L), and stirred for 24 h. After crystallization at 100 ° C. for 48 h in a hydrothermal reactor, the mixture was filtered, washed, and dried. After calcination at 550 ° C. for 6 h, a powder was obtained, namely mesoporous silica.
[0078] (2) 100 mg of cesium carbonate (0.3 mmol), 1 mL of oleic acid (3 mmol) and 10 mL of octadecene were fully reacted and dissolved under vacuum at 120° C. to obtain solution I;
[0079] (3) After 138 mg (0.38 mmol) of lead bromide, 10 mL of octadecene, 1 mL of oleic acid (3 mmol), and 1 mL of oleylamine (3 mmol) were fully dissolved at 120° C., 200 mg of mesoporous silica was added, and the mixture was fully immersed for 60 min to obtain solution II;
[0080] (4) 12 mL of solution II was heated to 190°C, and 1 mL of solution I was quickly injected. The reaction solution was obtained after stirring at the same temperature for 10 min. Finally, the final product was obtained by centrifugation, separation, and washing, which was recorded as CsPbBr3@SiO2 composite material.
[0081] Figure 1 This is the XRD spectrum of the product prepared in this example. By observing the spectrum, it can be confirmed that the product composition is CsPbBr3 and SiO2.
[0082] Figure 2 This is the SEM spectrum of the product prepared in this example. It can be seen from the figure that a fibrous CsPbBr3@SiO2 composite material with a length of 400-600nm and a diameter of 40-80nm is prepared.
[0083] Figure 3 This is a TEM image of the product prepared in this example. It can be seen from the figure that the pore diameter of the prepared CsPbBr3@SiO2 composite material is about 7nm, and CsPbBr3 perovskite quantum dots are evenly distributed inside.
[0084] Figure 4 This is the HRTEM image of the product prepared in this example. It can be seen from the figure that the size of the perovskite quantum dots in the prepared CsPbBr3@SiO2 composite material is about 4 to 5 nm and is evenly distributed in the pores.
[0085] The pore diameter distribution diagram of the product prepared in this example was tested by nitrogen adsorption method. Figure 5 As shown, it was observed that the pore diameter distribution was concentrated, mainly distributed in the range of 6 to 8 nm.
[0086] Figure 6 The SAXS spectrum of the product prepared in this example is shown in Figure 1. It is observed that the product prepared in this example has good order. The SAXS spectrum of the products prepared in Examples 3 and 4 is also shown in the figure. By comparison, it is found that as the crystallization temperature increases, the order of the prepared product decreases.
[0087] Performance Testing
[0088] 1. Light stability test:
[0089] The CsPbBr3@SiO2 composite material prepared in this embodiment was placed at room temperature 25°C and humidity 40% for 9 days and then tested using an FLS1000 spectrometer with the excitation light set to 365nm, the incident light grating to 1, and the output light grating to 0.7.
[0090] Figure 7 The graph of the luminescence intensity of the product prepared in this example over time shows that the composite material exhibits high spectral stability, and still maintains 91.6% of the luminescence intensity after one week. The specific values are listed in Table 1 below.
[0091] Table 1
[0092]
[0093] 2. Thermal stability test:
[0094] The CsPbBr3@SiO2 composite material prepared in this embodiment was subjected to variable temperature spectrum test using FLS1000, with the incident grating set to 0.5, the exit grating set to 0.5, the excitation light wavelength of 365nm, the heating rate of 10K / min, and liquid nitrogen cooling.
[0095] Figure 8The luminescence intensity of the product prepared in this example varies with temperature. In the figure, the temperature gradually increases in the direction of the arrow. The specific values are listed in the following Table 2. It is observed that at 100°C, the luminescence intensity is still 50% of the initial value, which is better than the 10% reported in the literature.
[0096] Table 2
[0097]
[0098] Comparative Example 1
[0099] The preparation process is basically the same as that in Example 1, except that the crystallization temperature in step (1) is replaced with 70°C.
[0100] Fig. 9 The SEM image of the product prepared in this comparative example shows that the prepared composite material is in the shape of short rods.
[0101] Fig.10 The graph of the luminescence intensity of the product prepared in this comparative example over time shows that the spectral stability of the composite material is poor, far lower than that of the composite material prepared in Example 1. The specific values are listed in Table 3 below.
[0102] Table 3
[0103]
[0104] Comparative Example 2
[0105] The preparation process is basically the same as that in Example 1, except that the crystallization temperature in step (1) is replaced with 150°C.
[0106] Fig.11 The TEM image of the product prepared in this comparative example shows that a large number of perovskite quantum dots grow outside the pores. This may be because the crystallization temperature is too high, resulting in a smaller pore size of the prepared mesoporous silica.
[0107] Comparative Example 3
[0108] The preparation process is basically the same as that in Example 1, except that in step (4):
[0109] The temperature of solution II was raised to 190° C., 1 mL of solution I was quickly injected, and the mixture was stirred at the same temperature for 40 min to obtain a reaction solution.
[0110] Fig.12 This is the XRD diagram of the product prepared in this comparative example. After testing, the product composition is CsPb2Br5.
[0111] Comparative Example 4
[0112] (1) 2 g of hexadecyltrimethylammonium bromide (CTAB) and 4.17 ml of TEOS were fully mixed in 480 ml of water, the pH was adjusted to 11 with 1 mol / L NaOH, stirred for 2 h, filtered, washed and dried, and heated at 550 °C for 6 h to obtain mesoporous silica;
[0113] (2) to (4) are exactly the same as in Example 1.
[0114] Fig.13 This is a TEM image of the product prepared in this comparative example. It can be seen that the prepared composite material is spherical.
[0115] Fig.14 The luminescence intensity of the product prepared in this comparative example changes with time. The stability is still inferior to that of Example 1. The specific values are listed in Table 4 below.
[0116] Table 4
[0117]
[0118] Comparative Examples 5-6
[0119] The preparation process is substantially the same as that in Comparative Example 4, except that in step (1), CTAB is replaced by equal amounts of tetradecyltrimethylammonium bromide and dodecyltrimethylammonium bromide, respectively.
[0120] According to TEM test, the composite materials prepared in Comparative Examples 5 and 6 were also spherical.
[0121] Example 2
[0122] The preparation process is basically the same as that in Example 1, except that the stirring time in step (4) is replaced with 20 min.
[0123] Fig.15 This is the TEM image of the product prepared in this example. After characterization, the morphology and size are basically consistent with those in Example 1.
[0124] Example 3
[0125] The preparation process is basically the same as that in Example 1, except that the crystallization temperature in step (1) is replaced with 125°C.
[0126] Fig.16 This is the pore diameter distribution diagram of the product prepared in this example. It can be seen that the pore diameter distribution is relatively concentrated, mainly distributed in the range of 6 to 7.3 nm.
[0127] Fig.17 The luminescence spectrum of the product prepared in this example changes with time, showing a high spectral stability. The specific values are listed in the following Table 5.
[0128] Table 5
[0129]
[0130] Example 4
[0131] The preparation process is basically the same as that in Example 1, except that the crystallization temperature in step (1) is replaced with 85°C.
[0132] Fig.18 This is the pore diameter distribution diagram of the product prepared in this example. It can be seen that the pore diameter distribution is relatively concentrated, mainly distributed in the range of 3 to 6 nm.
[0133] Fig.19 The luminescence spectrum of the product prepared in this example changes with time, showing a high spectral stability. The specific values are listed in the following Table 6.
[0134] Table 6
[0135]
[0136] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A fibrous mesoporous silica perovskite composite material, characterized in that: It includes fibrous mesoporous silica and perovskite quantum dots that are in-situ grown and uniformly distributed inside the pores of the fibrous mesoporous silica; The fibrous mesoporous silica has a plurality of pores which are parallel to each other but not interconnected, and the pores are through holes along the length direction of the fibrous mesoporous silica; The molecular formula of the perovskite quantum dot is CsPbX3, where X is selected from halogen.
2. The fibrous mesoporous silica perovskite composite material according to claim 1, characterized in that: The length of the fibrous mesoporous silica is 300-850 nm, the diameter is 30-90 nm, and the average diameter of several pores in the fibrous mesoporous silica is 3-9 nm; The size of the perovskite quantum dots is 4 to 6 nm.
3. The fibrous mesoporous silica perovskite composite material according to claim 2, characterized in that: The length of the fibrous mesoporous silica is 400-600 nm, the diameter is 40-80 nm, and the average diameter of several pores in the fibrous mesoporous silica is 6-8 nm; The size of the perovskite quantum dots is 4-5 nm.
4. A method for preparing the fibrous mesoporous silica perovskite composite material according to any one of claims 1 to 3, characterized in that: The steps include: (1) fully hydrolyzing a silicon source precursor and a pore-forming agent under acidic conditions to undergo a crystallization reaction, and then calcining at a high temperature to obtain mesoporous silica; The pore former is selected from a triblock copolymer of polyethylene oxide-polypropylene oxide-polyethylene oxide; (2) mixing a cesium precursor, oleic acid and octadecene until completely dissolved to obtain a solution I, mixing a lead halide, oleic acid, oleylamine and octadecene until completely dissolved, and then adding the mesoporous silica prepared in step (1) to obtain a solution II; (3) Rapidly injecting solution II into solution I, and obtaining the fibrous mesoporous silica perovskite composite material after sufficient reaction.
5. The method for preparing the fibrous mesoporous silica perovskite composite material according to claim 4, characterized in that: In step (1): The silicon source precursor is selected from one or more of tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane; The mass ratio of the pore former to the silicon source precursor is 1:(1.5-2.5); The pH value of the acidic condition is 1 to 2; The temperature of the crystallization reaction is 85-125°C; The high temperature calcination temperature is 400-700°C.
6. The method for preparing the fibrous mesoporous silica perovskite composite material according to claim 4, characterized in that: In step (2): The cesium precursor is selected from cesium carbonate and / or cesium acetate; In the solution I, the concentration of the cesium precursor is 0.02-0.04 mol / L; The molar ratio of the cesium precursor to oleic acid is 1:(10-15).
7. The method for preparing the fibrous mesoporous silica perovskite composite material according to claim 4, characterized in that: In step (2): The lead halide is selected from one or more of lead fluoride, lead chloride, lead bromide and lead iodide; In the solution II, the concentration of lead halide is 0.02-0.04 mol / L; The mass ratio of lead halide to mesoporous silica is 1:(0.7-2.2); The molar ratio of lead halide to oleic acid and oleylamine is 1:(10-15):(10-15).
8. The method for preparing the fibrous mesoporous silica perovskite composite material according to claim 4, characterized in that: In step (3): First heat solution II to 185-195°C and then quickly inject it into solution I; The time for full reaction is 10 to 20 minutes.
9. The method for preparing the fibrous mesoporous silica perovskite composite material according to claim 4, characterized in that: In step (3), the volume ratio of solution I to solution II is 1:(10-15).
10. The method for preparing the fibrous mesoporous silica perovskite composite material according to any one of claims 4 to 9, characterized in that: The temperature of the crystallization reaction is 100°C.
Citation Information
Patent Citations
Method for preparing stable perovskite quantum dot
CN107557004A
Perovskite quantum dot and mesoporous silica composite luminescent material and preparation thereof
CN114058367A
Strontium-doped perovskite quantum dot / mesoporous silica composite material and preparation thereof
CN114891504A
Perovskite quantum dot / mesoporous silica nano composite material, anti-counterfeiting ink and preparation method
CN116590010A
Spherical microporous silica porous particle and its manufacturing method
JP2004182492A
Cited By
Perovskite aerogel yarn and preparation method and application thereof
CN121931649A
Perovskite aerogel yarn and preparation method and application thereof
CN121931649B